PENENTUAN NILAI COLOUR GULA PRODUK PADA UNIT LUMP SEPARATOR DENGAN MENGGUNAKAN SPEKTROFOTOMETER VISIBLE DAN REFRAKTOMETER - Pevi Riani; Diana Triyanti Gultom (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2019)
Refined sugar is produced from raw sugar through refined processes for the needs of the food and beverage industry.The raw materials used are imported from the raw sugar producing countries of Australia, Brazil and Thailand. Quality control is caried out since the arrival of the material so that the material received is only material that meets the quality requirements.The most important process control in the process of refined sugar processing is during the decolorization process.In determining the color value the method used is visible spectrophotometry to determine the absorbance value and refractometryto determine the value of %brix. Based on the results of the determination made at PT Medan Sugar Industry obtained the average value of the color of sugar R1 products is 11.1 IU, the color value of sugar product R2 is 23.5 IU, the color value of sugar product R3is 33.2 IU, and the color value of sugar product R4 is 39.6 IU, when compared with the quality standards used, the value of the color of the sugar product meets the standars. The quality standard used is ICUMSA (International Commision for Uniform Methods of Sugar Analysis) with IU units (ICUMSA Unit) and testing of refined sugar products based on SNI.01.3140.2-2011.A.6 regarding the quality requirements of refined crystal sugar where grade A namely ≤45 IU and grade B which is 45-80 IU.